Konstelasi Pemikiran Hukum Keluarga di Tunisia - Fahmi Assulthoni (ASASI: Journal of Islamic Family Law, 2021)
Tunisia is one of the many Muslim countries that continue to strive to build a family law system which is a permanent rule of law for Muslims. Both before and after Tunisia's independence, legal reforms were intensively carried out, including legal reforms in the field of family law. One of the laws implemented in Tunisia is the Tunisian Code of Personal Status (CPST) or other names Majallah Al-Akhwal Ash-Shakhshiyyah. The legal reforms carried out by Tunisia cannot be separated from the progressive thoughts that have colored family law policies which in the next stage will become state policies. This article is presented in a descriptive form using a literature study approach as the study material. The results of the study concluded that the Tunisian State carried out many Islamic family law policies based on the development of family law in the world and the needs of its citizens.